HPV vaccination in Latin America: Coverage status, implementation challenges and strategies to overcome it - Nogueira-Rodrigues, Angélica; Flores, Matheus Gonçalves; Macedo Neto, Avelar Oliveira; Braga, Lucélia Antunes Coutinho; Vieira, Carolina Martins; Sousa-Lima, Renata Maria de; de Andrade, Diocésio Alves Pinto; Machado, Karime Kalil; Guimarães, Andrea Paiva Gadelha (Frontiers in Oncology, 2022)
Cervical cancer remains a leading cause of mortality amongst females in Latin America (LATAM). Cervical cancer is a preventable disease and HPV vaccination is a main key strategy towards elimination. This study analyzes the current status of HPV vaccine implementation and the main barriers to achieving adequate coverage in the region. We collected data regarding the nineteen sovereign states of LATAM (comprised of all Portuguese and Spanish-speaking nations located south of the United States). The following data for each country was collected: year of HPV vaccine implementation, gender and age targets, the number of doses included in the public program and coverage by dose. Sixteen out of the 19 evaluated countries have already implemented HPV vaccination programs. Despite its proven efficacy and safety, HPV vaccine uptake in Latin America has been lower than expected. There is an evident decline in compliance regarding the second dose. Some of the causes for the insufficient coverage are: limited knowledge of HPV and HPV vaccine; misguided safety concerns; high cost; cultural barriers; and the Covid19 pandemic. Proper strategies to overcome these barriers are needed to ensure successful uptake. Efective policies are: adopting the one dose schedule, delivering the vaccine on both health center and schools, and advising health professionals to recommend the vaccine. Further research regarding HPV vaccine hesitancy in Latin America is needed.